Choosing the tactics of surgical treatment of vascular leukomas based on impression cytology - I. A. Zlobin; S. V. Churashov; A. N. Kulikov; V. S. Chirsky; V. F. Chernysh; I. O. Gavrilyuk (Российский офтальмологический журнал, 2022)
Purpose: to provide clinical and morphological evaluation of the corneal epithelium phenotype in total vascular leukomas of varied etiologies and determine the optimal surgical treatment using impression cytology (IC).Materials and methods. 44 patients (44 eyes) with corneal vascular leukomas of various etiologies underwent optic keratoplasty preceded by IС. The patients were divided into 2 groups according to IC findings. Group 1 included 30 patients who were shown by IC to have corneal epithelium. These patients received penetrating keratoplasty (PK). Group 2 consisted of 14 patients whose epithelium was determined to be of conjunctival phenotype. Eight of group 2 patients had their corneal epithelium phenotype restored by limbal transplantation followed by PK. The remaining patients of group 2 were not operated for various reasons.Results. In the remote postoperative period (9–12 months after the operation) corrected visual acuity of group 1 patients ranged from 0.3 to 0.6 (ave. 0.450 ± 0.073). A relapse of corneal leukoma was observed in three patients of group 1 (10%). In group 2, a transparent vascular-free engraftment of keratotransplants was observed in 5 patients after limbal transplantation (the first stage of surgical treatment) and PK, their corrected visual acuity ranged from 0.1 to 0.5 (ave 0.37 ± 0.12), 1 (20%) patient had a relapse of the leukoma. Conclusions. Impression cytology is an acceptable and low invasive diagnostic technique that allows clinical and morphological evaluation of the epithelium phenotype that covers the vascular leukoma and helps determine validated indications for the choice of a surgical treatment technique for such patients.